Geochemical and Mineralogical Characteristics of Deep Porphyry Systems: Implications for Exploration Using ASTER - Michael Owenvbiugie Eguagie; Idoko Peter Idoko; Onuh Matthew Ijiga; Lawrence Anebi Enyejo; Francisca Chinonye Okafor; Chinelo Nwaamaka Onwusi (International Journal of Scientific Research in Civil Engineering, 2025)
Porphyry systems are critical sources of economically valuable metals, making their identification and exploration a key focus in mineral resource studies. Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) data have emerged as a powerful tool for mapping the geochemical and mineralogical characteristics of these systems, enabling more precise exploration efforts. This review examines the geochemical and mineralogical indicators of deep porphyry systems and evaluates the effectiveness of ASTER in their exploration. It begins by exploring the geological framework and alteration zones typical of porphyry deposits, emphasizing the unique advantages of ASTER in remote sensing applications. The methodology focuses on evaluating case studies where ASTER data were utilized to map alteration minerals and detect geochemical anomalies, alongside techniques for data processing and ground-truth validation. Results reveal that ASTER effectively identifies critical alteration zones and mineralogical features, though challenges remain in distinguishing overlapping mineral signatures in complex terrains. Recommendations include integrating ASTER with complementary geophysical and geochemical methods and advancing data processing techniques to enhance exploration accuracy. This study highlights ASTER’s significant potential in driving efficient and sustainable exploration of deep porphyry systems.